THE EFFECT OF TAX INCENTIVES ON INCREASING THE TAX BASE - Sherzod Uralovich Kiyosov (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
the article describes the essence of tax benefits, the organization of tax services in providing them, the priority areas of tax services. Proposals and recommendations for improvement in the direction of modernization of production of tax benefits, technical renewal and diversification, wide introduction of innovative technologies have been developed.